Local Recurrence Outcomes of Colorectal Cancer Oligometastases Treated With Stereotactic Ablative Radiotherapy. (17th November 2021) - Benson, Kathryn R.K.; Sandhu, Navjot; Zhang, Carrie; Ko, Ryan; Toesca, Diego A.S.; Lee, Phoebe E.; Von Eyben, Rie; Diehn, Maximilian; Gensheimer, Michael; Maxim, Peter G.; Bush, Karl; Loo, Billy W.; et al.
Abstract : Purpose: The aim of this study was to report local failure (LF) outcomes and associated predictors in patients with oligometastatic colorectal cancer (CRC) treated with stereotactic ablative radiotherapy (SABR). Materials and Methods: We retrospectively reviewed patients with CRC metastases to the brain, liver, spine, or lung treated with SABR between 2001 and 2016. Time to LF was summarized using cumulative incidence of LF curves with death as a competing risk. Results: The analysis included a total of 130 patients and 256 lesions. Of the metastases treated, 129 (50%) were brain, 50 (20%) liver, 49 (19%) spine, and 28 (11%) lung. Median gross tumor volume was 24 mL for liver metastases, 2 mL for brain metastases, 4 mL for spine metastases, and 1 mL for lung metastases. The overall 1, 2, and 3-year cumulative incidence of LF rates were 21.6% (16.5, 27.1), 28.2% (22.3, 34.4), and 31.5% (25.2, 38.0), respectively. LF was highest among the liver metastases (1 y: 26.0%, 2 y: 38.5%), followed by spine (1 y: 25.1%, 2 y: 31.1%), brain (1 y: 20%, 2 y: 25.2%), and lung (1 y: 13.7%, 2 y: insufficient data). Metastases from right-sided primary CRC were significantly more likely to have LF ( P =0.0146, HR=2.23). Biologically effective dose>70 Gy, defined using a standard linear quadratic model using α/β ratio of 10 on the individual lesion level, and pre-SABR chemotherapy were also significant predictors of LF ( P = 0.0009 and 0.018, respectively). Conclusions: CRC metastases treated with SABR had significantly higher rates of LF if they originated from right-sided primary CRC, compared with left-sided. Liver metastases had the highest rates of LF compared with other metastatic sites. Thus, CRC liver metastases and metastases from right-sided CRC may benefit from more aggressive radiotherapy.